2021
DOI: 10.3389/fmicb.2021.766138
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Nanoparticles Prime a Protective Immune Response in Galleria mellonella to Defend Against Candida albicans

Abstract: Purpose: Zinc oxide nanoparticles (ZnO-NPs) have exerted antimicrobial properties. However, there is insufficient evaluation regarding the in vivo antifungal activity of ZnO-NPs. This study aimed to investigate the efficacy and mechanism of ZnO-NPs in controlling Candida albicans in the invertebrate Galleria mellonella.Methods:Galleria mellonella larvae were injected with different doses of ZnO-NPs to determine their in vivo toxicity. Non-toxic doses of ZnO-NPs were chosen for prophylactic injection in G. mell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…For all particle concentrations, a survival rate of 100% was observed ( Figure 2 a). This observation agrees with the range of efficacy and non-toxicity reported for non-green-synthesised ZnO NPs in Galleria mellonella [ 11 , 12 ].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…For all particle concentrations, a survival rate of 100% was observed ( Figure 2 a). This observation agrees with the range of efficacy and non-toxicity reported for non-green-synthesised ZnO NPs in Galleria mellonella [ 11 , 12 ].…”
Section: Resultssupporting
confidence: 91%
“…An in vivo study on Helicoverpa armigera larvae revealed the toxicity of green-synthesised ZnO NPs when using neem leaf extracts at doses up to 200 mg/kg [ 9 ]. Multiple in vivo studies on Galleria mellonella larvae have also reported the toxicity of conventionally synthesised ZnO NPs [ 10 , 11 , 12 , 13 ]. Eskin et al [ 11 ] reported pulpal toxicity at concentrations greater than 1000 mg/kg while observing extended adult longevity at concentrations as high as 5000 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of C. albicans , the fungicidal effect of ZnO NPs + UV-B at 1, 2, and 3 min reached 100 % and was statistically significant against the negative control. A previous study using an InVivo model to determine the phagocytic response of G. mellonella after infection by C. albicans used ZnO NP at 0.2 mg/kg, reducing mortality up to 13 % compared to the negative control (p < 0.05), and when used at concentrations of 2 mg/kg all infected larvae survived, also demonstrating good tolerance to the concentrations tested [ 58 ]. This demonstrates the effectiveness of ZnO nanoparticles and the tolerance of eukaryotic cells to these nanoparticles.…”
Section: Discussionmentioning
confidence: 99%